Red fleshed guava enriching its germplasm - Kumar, Rakesh; Bakshi, Parshant; Sharma, Jagpal; Singh, V B; Sharma, Sushil (Indian Horticulture, 2019)
There is a rich genetic diversity in red-fleshed germplasm of guava of local inhabitants and at growers’ fields in Jammu subtropics. The indigenous germinated strains are gaining more popularity due to their red-fleshed pulp, good taste, excellent aroma, high TSS%, fruit size and medicinal value. The maximum areas in these regions are established naturally occurring superior germplasm which is propagated through seed from meritorious indigenous guava plants. Nevertheless, diversity of guava germplasam can be used through selection and evaluation of outstanding material having comparative advantage to improve its productivity.